Right to image, public agents and media: impacts on protecting the image of suspects after the new law of abuse of authority (Research, Society and Development, 2021)
The right to image protects the physical representation of the body and the characteristic features by which a person can be recognized. Suspects of committing crimes suffered violations of this right by the media and public officials. This violation influenced public opinion, allowing citizens to be judged prematurely, without the right to a defense and the presumption of innocence. The difficulties in protecting the right to image pointed to the need for its regulation by the legal system, which recently occurred with the enactment of Law 13,869/2019, known as the new law of abuse of authority. Thus, the objective of the research is to investigate whether article 13 of Law 13.869/2019 has impacted the performance of public agents of the State of Pernambuco and the media discourse regarding the non-violation of the right to image. The methodology used in the research will be the content analysis of news about police operations, in the fight against the crime of drug trafficking in the state of Pernambuco, disseminated on the websites of the main programs that present police actions in the state, namely: Por dentro com Cardinot (TV Jornal/SBT) and Balanço Geral PE (TV Clube/Rede Record), in the period between 2019 and 2020. Thus, it is expected that it will be possible to conclude whether there was an impact on the protection of suspects' image after the implementation of the law.